IMPLEMENTASI INTERNET OF THINGS UNTUK ALAT PEMBERIAN MAKAN IKAN OTOMATIS DAN MONITORING SUHU AIR - Thorikul Sidiq , Mukti; Heru Mujianto , Ahmad (Inovate, 2023)
The maintenance of ornamental fish is currently quite popular among many people. Proper care must be carried out to ensure that the fish can grow and develop healthily. One important aspect to consider is the accuracy in providing regular feedings and maintaining the water temperature in the aquarium. However, busy schedules or time constraints often hinder the regular feeding of fish, leading to irregular feedings. Additionally, the condition of the aquarium must also be monitored, such as maintaining the water temperature at a safe level for the fish's health. The implementation of the Internet of Things (IoT) is used as a monitoring and control system for this device. This research is conducted to address the weaknesses of the manual fish feeder system and the lack of attention to water temperature. This device is also a development from previous research aimed at improving the effectiveness of fish care. The testing results have concluded the performance of this device. The device functions well as an automatic fish feeder according to the predetermined schedule and can monitor water temperature through the Bylink application. With the use of microcontroller and IoT, this automatic fish feeder and water temperature monitoring device can be implemented. It is expected that this device will enable fish owners to feed their fish more regularly and timely and accurately monitor the water temperature, thus making fish maintenance more effective. Keywords: Fishkeeping, Internet of Things (IoT), temperature monitoring, Blynk application, microcontroller.